Impact of Social Media Marketing and Electronic Word of Mouth (E-WOM) on Purchase Intention in the Culinary Sector: Systematic Literature Review - Muchammad Ardhianto, Putra (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
This paper presents a systematic literature review (SLR) on the impact of social media marketing and electronic word of mouth (E-WOM) on purchase intention in the culinary sector, with a focus on the mediating role of trust. As digital platforms increasingly influence consumer behavior, understanding how social media marketing and E-WOM shape purchase decisions is essential for culinary businesses aiming to enhance their market presence. The review synthesizes existing research on how social media marketing strategies and online reviews or recommendations from peers influence consumer trust, which in turn affects their purchase intention. The findings suggest that both social media marketing and E-WOM play critical roles in building trust, which directly enhances consumers’ intention to purchase culinary products. The paper also highlights research gaps and provides actionable insights for marketers in the food industry seeking to optimize digital strategies for consumer engagement and sales growth.